Influence of Marketing Mix and Attitude on Seawed Snack Purchase Decision Among Child Consumer - Susilo Hadi; Ujang Sumarwan; Lilik Noor Yuliati (Green Publisher Indonesia, 2026)
This study investigates the influence of the marketing mix—product, price, place, and promotion—and consumer attitudes on the purchasing decisions of seaweed snacks among child consumers in Indonesia. It responds to the limited research on children’s purchasing behavior, particularly within the healthy snack segment, by examining how marketing elements shape attitudes and drive buying actions. Using a quantitative survey method, data were collected from 212 respondents aged 8–15 years in Jakarta and surrounding areas and analyzed through Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that most consumers are elementary school children aged 8–12 years who moderately consume seaweed snacks, with average spending per purchase ranging from IDR 13,000–14,000. The marketing mix significantly influences children’s positive attitudes; however, only price and attitude directly affect purchasing decisions. Product, price, and promotion indirectly affect purchase behavior through attitude as a mediating variable, while place shows no significant mediating effect. The study underscores that effective marketing strategies for children should prioritize trustworthy product quality, credible health claims, appropriate pricing, and engaging promotional approaches. These insights contribute to a deeper understanding of child consumer behavior in Indonesia’s growing healthy snack market.